Faktore by die oorweging van kredietverlening in verbruikersbankwese - P. L.S. Ackermann; W. P.J. Van Rensburg (South African Journal of Business Management, 1985)
– Factors in considering the granting of credit in consumer banking In this study the authors attempt to identify underlying factors from various evaluation criteria (as observed by bank managers) in considering the granting of credit in consumer banking with regard to the various race groups of the Republic of South Africa. The sample consists of 510 managers from the consumer division of general and commercial banks. With the aid of principal factor analysis six underlying factors are identified with respect to Indians, whereas five underlying factors are identified with regard to coloureds, whites and blacks.
Keywords: 650